Effect of Implantation and Fixation of Mirena in the Treatment of Adenomyosis and its Influence on Serum Inflammatory Factors: Mirena effects on adenomyosis and inflammatory factors - Leilei, Gong; Di, Xin; Na, Li; Rong, Shao (Cellular and Molecular Biology, 2022)
This experiment was carried out to analyze the placement and fixation of Mirena in the treatment of adenomyosis (AM) and its influence on the level of serum inflammatory factors in patients. For this purpose, the subjects of this study were 100 AM patients hospitalized in our hospital from June 2019 to June 2021. They were divided into two groups according to the lottery method (n=50 for each group). The control group was treated with intramuscular triptorelin after the operation, and the observation group was treated with Mirena during the operation. Sex hormone indexes, VAS score, uterine volume, serum inflammatory indexes, the total incidence of adverse reactions, WHOQOL-BREF score and recurrence rate were compared between the two groups. Results showed that in the observation group after treatment E2VAS score and uterine volume were lower, serum IL-8 and TNF-A were lower, the whoqOL-BREf score was higher, and the recurrence rate (0) was lower than that in the control group (12.00%). The total incidence of adr in the observation group (4.00%) was lower than in the control group (8.00%). Then intraoperative placement of Mirena can effectively regulate sex hormone indexes of AM patients, reduce uterine volume, relieve dysmenorrhea symptoms, reduce the inflammatory response, improve quality of life, and reduce recurrence rate, without obvious adverse reactions.